2016
DOI: 10.1088/1367-2630/18/4/043027
|View full text |Cite
|
Sign up to set email alerts
|

How discord underlies the noise resilience of quantum illumination

Abstract: The benefits of entanglement can outlast entanglement itself. In quantum illumination, entanglement is employed to better detect reflecting objects in environments so noisy that all entanglement is destroyed. Here, we show that quantum discord-a more resilient form of quantum correlationsexplains the resilience of quantum illumination. We introduce a quantitative relation between the performance gain in quantum illumination and the amount of discord used to encode information about the presence or absence of a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 39 publications
3
86
0
Order By: Relevance
“…In [271], the accuracy of the discrimination between two states ρ 0 and ρ 1 with a priori probabilities p 0 and p 1 , respectively, has been quantified by the corresponding Shannon distinguishability, i.e., D H (ρ 0 , ρ 1 ) := max M J(X : X In a quantum illumination protocol assisted by non-classical correlations, the sender improves their strategy by maximally entangling the probe A with an idler ancilla B (which is retained at the sending station) by creating the pure global state ρ ψ AB = |ψ ψ| AB , where…”
Section: State Discrimination and Quantum Illuminationmentioning
confidence: 99%
See 1 more Smart Citation
“…In [271], the accuracy of the discrimination between two states ρ 0 and ρ 1 with a priori probabilities p 0 and p 1 , respectively, has been quantified by the corresponding Shannon distinguishability, i.e., D H (ρ 0 , ρ 1 ) := max M J(X : X In a quantum illumination protocol assisted by non-classical correlations, the sender improves their strategy by maximally entangling the probe A with an idler ancilla B (which is retained at the sending station) by creating the pure global state ρ ψ AB = |ψ ψ| AB , where…”
Section: State Discrimination and Quantum Illuminationmentioning
confidence: 99%
“…In [271] an answer has been provided by showing a direct equality between the performance gain in quantum illumination over any conventional illumination protocol and the amount of quantum discord between the probe and its ancilla which is consumed to detect the target, thus linking the expenditure of QCs to the resilient enhancement of quantum illumination. More precisely:…”
Section: State Discrimination and Quantum Illuminationmentioning
confidence: 99%
“…Although the thermal noise destroys the entanglement, theory showed that the QI system will significantly outperform a classical (coherent-state) system of the same transmitted energy [5][6][7]. Later, a QI protocol was proposed for secure communication [8] whose experimental realization [9] showed that entanglement's benefit could, indeed, survive an entanglement-breaking channel.…”
mentioning
confidence: 99%
“…Achieving this in a cheap and reliable way is essential to the development of future quantum technologies. They also reinforces the role of quantum discord as a beneficial and practically relevant quantity [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]: as discord appears to bound the entanglement gain and to allow for excessive entanglement distribution, it emerges as a key player of fundamental relevance in the context of quantum communication and networking.…”
Section: Discussionmentioning
confidence: 54%